Impaired Retrograde Transport Due to Lack of TBC1D5 Contributes to the Trafficking Defect of Lysosomal Cathepsins in Ischemic/Hypoxic Cardiomyocytes - Cui, Lin; Zhang, Qiong; Huang, Yao; Yang, Lei; Zhang, Junhui; Jiang, Xupin; Jia, Jiezhi; Lv, Yanling; Zhang, Dongxia; Huang, Yuesheng (Frontiers in Cardiovascular Medicine, 2021)
Lysosomal dysfunction has been found in many pathological conditions, and methods to improve lysosomal function have been reported to be protective against infarcted hearts. However, the mechanisms underlying lysosomal dysfunction caused by ischemic injury are far less well-established. The retromer complex is implicated in the trafficking of cation-independent mannose 6-phosphate receptor (CI-MPR), which is an important protein tag for the proper transport of lysosomal contents and therefore is important for the maintenance of lysosomal function. In this study, we found that the function of retrograde transport in cardiomyocytes was impaired with ischemia/hypoxia (I/H) treatment, which resulted in a decrease in CI-MPR and an abnormal distribution of lysosomal cathepsins. I/H treatment caused a reduction in TBC1D5 and a blockade of the Rab7 membrane cycle, which impeded retromer binding to microtubules and motor proteins, resulting in an impairment of retrograde transport and a decrease in CI-MPR. We also established that TBC1D5 was an important regulator of the distribution of lysosomal cathepsins. Our findings shed light on the regulatory role of retromer in ischemic injury and uncover the regulatory mechanism of TBC1D5 over retromer.